Brewing Justice: Fair Trade Coffee, Sustainability, and Survival - Daniel Jaffee (University of California Press, 2014)
The chance to revisit the issues, places, and relationships described in Brewing Justice after seven years is a wonderful opportunity and at the same time a formidable challenge. The political landscape of the fair-trade movement and market has in many ways been altered dramaticallyâ€”its scale and scope greatly expanded, its key institutions reshaped, and its center of gravity shifting toward new consumers, geographies, commodities, and forms of production. Yet there is also stability: many pioneering firms and NGOs remain deeply involved, and the general terms of the struggle over the movementâ€™s future direction, indeed its soul, remain remarkably consistent. It is these tensions and divergences that I aim to explore in this revised edition. I am grateful to University of California Pressâ€”and especially to my editor Naomi Schneiderâ€”for this invitation to reassess the state of the social relationships embodied in fairtrade coffee. Beyond a doubt, many more consumers are now aware of fair trade. Global sales of all fair-trade-certified goods have more than quadrupled since the statistics cited in the original edition, from $1.3 billion in 2005 to $3.3 billion in 2007 and over $7 billion in 2012. Many more mainstream consumers now have access to fair-trade products, with much of this growth occuring through mass-market brands and mainstream retail channels. Yet through this mainstreaming process, the fair-trade systemâ€™s embrace of conventional market actorsâ€”transnational agrifood corporations such as Dole and NestlÃ©, as well as the largest global retail-ers, including Walmart and McDonaldâ€™sâ€”a process already well underway by 2007, has become more pronounced and entrenched. The power of these firms to influence the content of fair-trade certification has increased, and many longtime participants allege that standards have been correspondingly weakened. Simultaneously, there has been an increase in the certification of crops produced under fair tradeâ€™s â€œhired laborâ€ modality by waged laborers on agribusiness plantations, rather than small farmers organized into democratic cooperatives or associations. As a result of these trends and others, the certification of fair-trade goods is now more complex and contested than it was seven years ago. This is especially true in the United States, where a major institutional splitâ€”Fair Trade USAâ€™s recent decision to break from the international fair-trade system and create its own standardsâ€”has roiled the movement, dividing activists and commercial firms alike. The updated edition examines how this schism has unfolded and explores the repercussions. As a result of these developments, consumers in the United States now face a proliferation of competing fair-trade labels and claims, making the fair-trade market increasingly challenging to navigate.